Exploratory Factor Analysis for The Development of The 49-Item Children’s Reading Motivation Scale (Crms-49) - Ontok-Balah, Khadiguia (International Research-Based Education Journal, 2024)
Reading is crucial and serves as a fundamentalbuilding block for learning. There are different instrumentsavailable to assess the reading motivation of grade school childrenbut, caution and careful thought is required because the validity andreliability of these measures cannot be generalized for use due tocultural and contextual differences. The aim of the study was tocreate a valid and reliable self-report measure of the readingmotivation of 280 intermediate-grade school pupils. The results ofthe analysis confirmed that the 49-item Children’s ReadingMotivation Scale (CRMS) developed in this study accounted for28.4% of the variance with three factors such as children's readingself-efficacy, parental autonomy-supportive reading practices, andchildren's reading and behavioral problems. The Cronbach’s α ofthe tool was between 0.793 to 0.864 among the three factorsidentified. The measure obtained good construct validity and willprove a useful tool to help Filipino teachers determine theintermediate graders’ motivation to read through their self-efficacyin reading, support practices of their parents in reading, and theirreading and behavioral problems.